Influence of Market Segmentation on Fashion Products on Profitability Levels with Marketing Strategies Through Social Media and E-Commerce - Cika Alpi Nurpauji; Muhammad Raihan Alghazli; Saddina Yosi Khoirusifa; Ghamar Hafidz; Salsa Reviansyah (JUSTINFO | Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
This research shows that market segmentation and marketing strategies through social media and e-commerce can increase the profitability of fashion products. According to BPS data for 2023, there is a significant increase in the purchase of fashion products in Indonesia. Based on the literature, this research discusses the concepts of market segmentation and marketing strategy. The approach through social media and e-commerce is one of the most effective ways to reach a wider target market and increase profitability. The results show a strong relationship between market segmentation, digital marketing strategy, and the profitability of fashion products. With fierce competition, changing trends, and expanding market reach, implementing these strategies is critical to the success of fashion companies in increasing sales and profitability. Players in the fashion industry anticipate this research to offer valuable insights for enhancing their marketing strategies.